Prehistory without borders the prehistoric archaeology of the Tyne-Forth region - Crellin, Rachel; Fowler, Chris 1973-; Tipping, Richard M. (Oxbow Books, 2016)
"Modern borders of all kinds, political, geographical and social, effect the kinds of prehistoric narratives archaeologists can write. Borders that dominate today did not exist in prehistory. This volume works across such borders and focuses specifically on the region between the Rivers Forth and Tyne, an area divided by the modern political border between Scotland and England. The introduction and opening chapters consider the impact of the Anglo-Scots and similar borders on our understanding of prehistoric patterns of activity. The introduction also asks whether, when, and to what extent this could be considered a coherent region in the prehistoric past. Further chapters explore the history of research in the region, including field survey and aerial photography. Another nine chapters discuss the results of recent research, including new and older excavations, or conduct regional analyses of artefacts and mortuary practices, starting with the Late Upper Palaeolithic and continuing with studies from the Early Neolithic through to the Late Iron Age. Taken as a whole, the publication suggests that while there was no coherent Tyne-Forth region in prehistory, except for perhaps in the Late Iron Age, research at this regional scale provides a strong basis for appreciating past cultural interaction at a variety of scales"...From publisher's website
Includes bibliographical references
Keywords: Vor- und Frühgeschichte; Funde; Prehistoric peoples -- Scotland -- Tyne, River, Region; Prehistoric peoples -- Scotland -- Forth, River, Region; Prehistoric peoples -- Scottish Borders (England and Scotland); Excavations (Archaeology) -- Scotland -- Tyne, River, Region; Excavations (Archaeology) -- Scotland -- Forth, River, Region; Social archaeology -- Scotland -- Tyne, River, Region; Social archaeology -- Scotland -- Forth, River, Region; Archäologie; Schottland; Tyne, River, Region (Scotland) -- Antiquities; Forth, River, Region (Scotland) -- Antiquities; Scottish Borders (England and Scotland) -- Antiquities; Forth -- Fluss; Tyne; Aufsatzsammlung